Actoprotective activity research of 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetates - A. A. Safonov; A. V. Nevmyvaka (Zaporozhye State Medical University, 2020)
Severe fatigue can occur due to overwork, lack of exercise, depression, insomnia, etc. It should be understood that fatigue, weakness, both emotional and physical, is not a disease. Often, actoprotective substances are used to reduce fatigue. To search for new substances with a different spectrum of pharmacological activity, 1,2,4-triazole derivatives have proven themselves well. The aim of work was to investigate actoprotective activity among previously synthesized 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetates. Materials and methods. The compounds used to study pharmacological activity were synthesized at the Department of Natural Sciences for International Students and Toxicological Chemistry ZSMU. White nonlinear rats weighing 200-260 g of 7 animals per group were used to study the actoprotective activity of 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetates. As a method for the study of pharmacological activity was used the method of forced swimming with a load of 10 % by weight of the rat. Statistical results were calculated using Kolmogorov-Smirnov test and Shapiro-Wilk test. Results. Compounds Ia, Ib, IIb, IIk, IIj had been found to have a moderate actoprotective effect. But none compound had exceeded the comparison drug. Some conclusions were drawn regarding the dependence of "structure - actoprotective effect": the most active compound was 2-aminoethanol 2-((5-(2-bromophenyl)-4-ethyl-4H-1,2,4-triazole-3-yl)thio)acetate (IIj); conversion to 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetate salts and selection as sodium, potassium, or 2-aminoethanol cations was resulted in to increase the actoprotective effect. Conclusions. As a result, the actoprotective activity of 18 new 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetates was investigated. Some conclusions were drawn regarding the dependence of "structure - actoprotective effect".